Study on the Awareness of the Installation of Lightning Protection System (LPS) By Using Structural Bonding Method (SBM) in the Building among Civil Engineering Consultants. - Syahirah Ismail (School of Environmental Engineering, University Malaysia Perlis, 2016)
To study the Awareness of the Installation of Lightning Protection System (LPS) by using Structural Bonding Method (SBM) among Civil Engineer. To study the Understanding of the Installation of Lightning Protection System (LPS) by using Structural Bonding Method (SBM) among Civil Engineer. To identify the recommendation and Suggestion from the Civil Engineer for the Structural Bonding Method (SBM).